Genomic Properties and Temporal Analysis of the Interaction of an Invasive Escherichia albertii With Epithelial Cells - Romão, Fabiano T.; Martins, Fernando H.; Hernandes, Rodrigo T.; Ooka, Tadasuke; Santos, Fernanda F.; Yamamoto, Denise; Bonfim-Melo, Alexis; Jones, Nina; Hayashi, Tetsuya; Elias, Waldir P.; Sperandio, Vanessa; Gomes, Tânia A. T. (Frontiers in Cellular and Infection Microbiology, 2020)
Diarrhea is one of the main causes of infant mortality worldwide, mainly in the developing world. Among the various etiologic agents, Escherichia albertii is emerging as an important human enteropathogen. E. albertii promote attaching and effacing (AE) lesions due to the presence of the locus of enterocyte effacement (LEE) that encodes a type three secretion system (T3SS), the afimbrial adhesin intimin and its translocated receptor, Tir, and several effector proteins. We previously showed that E. albertii strain 1551-2 invades several epithelial cell lineages by a process that is dependent on the intimin-Tir interaction. To understand the contribution of T3SS-dependent effectors present in E. albertii 1551-2 during the invasion process, we performed a genetic analysis of the LEE and non-LEE genes and evaluated the expression of the LEE operons in various stages of bacterial interaction with differentiated intestinal Caco-2 cells. The kinetics of the ability of the 1551-2 strain to colonize and form AE lesions was also investigated in epithelial HeLa cells. We showed that the LEE expression was constant during the early stages of infection but increased at least 4-fold during bacterial persistence in the intracellular compartment. An in silico analysis indicated the presence of a new tccP/espFU subtype, named tccP3. We found that the encoded protein colocalizes with Tir and polymerized F-actin during the infection process in vitro. Moreover, assays performed with Nck null cells demonstrated that the 1551-2 strain can trigger F-actin polymerization in an Nck-independent pathway, despite the fact that TccP3 is not required for this phenotype. Our study highlights the importance of the T3SS during the invasion process and for the maintenance of E. albertii 1551-2 inside the cells. In addition, this work may help to elucidate the versatility of the T3SS for AE pathogens, which are usually considered extracellular and rarely reach the intracellular environment.